EVALUATION OF CASPASE 3 AS AN INDICATOR FOR BREAST CANCER CHEMOTHERAPY RESPONSE - Siregar, Kamal Basri; Manuaba, Tjakra Wibawa; Lubis, Muhammad Najib Dahlan; Sembiring, Rosita Juwita (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: This study aimed to assess the difference of postchemotherapy caspase 3 level between triple negative breast cancer (TNBC) subjects with and without clinical response. Methods: A total of 48 subjects with intraductal and 12 subjects with intralobular TNBC who were undergoing surgery at Adam Malik General Hospital were analyzed the response of neoadjuvant chemotherapy. Postsurgical breast tumor tissue was treated in pathology laboratory for caspase 3 analysis. The data were processed in SPSS 22 with significance limitation of 0.05. Results: Median levels of caspase 3 postchemotherapy were higher both in intraductal and intralobular TNBC subtype (6 vs. 4.5 and 5 vs. 3, respectively) responsive group, while no changes detected in the group without clinical response. In statistical analysis, there was a significant difference of caspase 3 level postchemotherapy only in group with clinical response (p=0.005 in intraductal carcinoma and p=0.0031 in intralobular carcinoma). Conclusion: Postchemotherapy caspase 3 level increased significantly in TNBC, either intraductal or intralobular subtype, subjects with clinical response, but not in subjects without clinical response. Â